Young women’s accounts of intimate partner violence in cohabiting relationships in Vhembe District, Limpopo Province - Makongoza, Matamela Fulufhelo Beatrice (University of the Witwatersrand, Johannesburg, 2024)
This thesis explores young women’s accounts of intimate partner violence in cohabiting relationships in Vhembe District, Limpopo Province. The constructivism paradigm aided in understanding young women’s experiences of intimate partner violence in cohabitating relationships and how these women navigate their lives in a cultural context that denounces cohabitation, making them vulnerable to possible gender-based violence. Cultural discourse can guide how young women make meaning and respond to their experiences of violence. This study suggests the intersectionality of different African philosophical lenses, including African psychological perspective, Ubuntu, and Vygotsky’s cultural historical activity theory (CHAT). There have been studies on intimate partner violence among young women in South Africa which report on the nature, extent, and severity of intimate partner violence against young women. Scholars focused their research on intimate partner violence against young women in boyfriend- and-girlfriend type relationships from different contextual backgrounds. Some studies also report on the experiences of violence in cohabitation relationships although these were not specifically focused on the context. This qualitative study presents the nature and forms of violence experienced by 10 young women between the ages and 18 and 24 years in cohabiting relationships in the rural Vhembe District, Limpopo Province. Young women were enlisted from the Thohoyandou Victim Empowerment Programme. Thematic analysis was used. Although cohabitation is not a new phenomenon in heterosexual relationships, violent incidences in cohabitation relationships are a trend in Africa. Young women reflected on their experiences of intimate partner violence within a cultural context that condemns cohabitation, referring to it as matula (taboo). They acknowledged living in a challenging time, and that forms of violence escalate the already existing problems. They also talked about the dangers of leaving an abusive partner, raised concerns about bystander issues, and shared that some spaces – both private and public – contribute to intimate partner violence against young women, instilling fear in these women. This study presents that young women in cohabiting relationships are more vulnerable because the nature of these relationships is not culturally acknowledged by parents and communities in general. Similarly, some African studies documented in this study found that it is better for young women to denounce cohabiting relationships and opt for marriage instead, or else they risk being disowned by their parents. This research shows that community factors such as gender inequality, social norms which accept violence, lack of support, and financial dependency on the partner contribute to the vulnerability of young women in cohabiting relationships. Interventions which prevent the implementation of rigid cultural norms and traditions, and which change the attitudes of individuals towards intimate partner violence may prevent the escalation of intimate partner violence in general. This study proposes that doing away with bystanders doing nothing, embracing relationship diversity, and revisiting the practice of Ubuntu could reduce the escalation of intimate partner violence.
A research report Submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Young women; intimate partner violence; cohabitation; Vhembe District; African philosophies; SDG-5: Gender equality